Analysis of Blockchain-Technology - Dvorchuk, Danylo; Shpinareva, Iryna (Kìbernetika ta komp'ûternì tehnologìï (Online), 2025)
Introduction. Blockchain technology has emerged as a transformative innovation in distributed computing, providing a secure, transparent, and decentralized mechanism for data management. Initially introduced as the backbone of cryptocurrencies, blockchain has expanded into various sectors, including finance, healthcare, supply chain management, and governance. However, despite its numerous advantages, blockchain faces significant challenges, including scalability, transaction speed, and energy consumption. This article presents a comprehensive analysis of blockchain technology, focusing on its classification, consensus mechanisms, scalability solutions, and future trends. The study explores the comparative advantages and limitations of different blockchain architectures and evaluates emerging optimization techniques such as hybrid consensus algorithms and artificial intelligence-based enhancements. Purpose of the Work. The objective of this study is to conduct an in-depth analysis of blockchain technology, investigating its core principles, operational mechanisms, and performance optimization strategies. The research aims to provide a systematic comparison of consensus algorithms, including Proof of Work (PoW), Proof of Stake (PoS), Delegated Proof of Stake (DPoS), and Byzantine Fault Tolerance (BFT) variations, assessing their impact on transaction speed, energy efficiency, and security. Additionally, the study examines Layer 1 (L1) and Layer 2 (L2) scaling solutions such as sharding, rollups, and sidechains to address blockchain's scalability challenges. The research also highlights emerging trends in blockchain development, particularly hybrid models and AI-driven optimization techniques, which can enhance blockchain efficiency and security. Results. The analysis reveals that different blockchain architectures exhibit varying trade-offs between decentralization, security, and scalability. Public blockchains, such as Bitcoin and Ethereum, prioritize decentralization and security but suffer from limited scalability. Private blockchains, in contrast, offer higher transaction throughput but compromise decentralization. Hybrid blockchains aim to balance these aspects by integrating the strengths of both models. A detailed comparison of consensus mechanisms indicates that PoW, while highly secure, is energy-intensive and slow, whereas PoS and its variations provide faster and more energy-efficient alternatives. The study also finds that Byzantine Fault Tolerance-based mechanisms, such as PBFT and DBFT, offer high-speed consensus suitable for enterprise applications. Furthermore, Layer 1 improvements, including sharding, enhance on-chain transaction processing, while Layer 2 solutions, such as optimistic rollups and zero-knowledge rollups, significantly increase throughput by offloading computations to secondary layers. The research highlights recent advancements, such as AI-assisted transaction validation and adaptive consensus algorithms, as promising directions for blockchain scalability and security. Conclusions. The study underscores the importance of optimizing blockchain scalability and consensus mechanisms to enable broader adoption across industries. While Layer 1 and Layer 2 solutions provide significant improvements in throughput and efficiency, their integration remains a key challenge. The findings suggest that hybrid consensus models and AI-based optimizations could further enhance blockchain performance, reducing energy consumption while maintaining security and decentralization. Future research should focus on developing dynamic sharding techniques, parallel consensus mechanisms, and predictive analytics for transaction management to advance blockchain's applicability in large-scale real-world scenarios. The continued evolution of blockchain technology will play a critical role in shaping secure, efficient, and decentralized digital ecosystems. Keywords: blockchain, decentralization, consensus mechanisms, optimistic rollups, sharding, transaction validation.